Legislative incorporation and dissolution of Regional Governance: The Case of Pahang Tenggara Development Authority, Malaysia - Wan Nazrul Helmy, Wan Mohd Zain (College of Local Administration, Khon Kaen University, 2022)
The aftermath of the May 13, 1969 racial riot in Malaysia saw the realignment of the Federal Government through the introduction of the New Economic Policy (NEP) that was embedded in the Second Malaysia Plan (1971-1975), focusing on poverty eradication, social reorganization and suppression of communist insurgency. Through NEP, seven regional development authorities, namely Pahang Tenggara Development Authority (DARA), Johor Tenggara Development Authority (KEJORA), Terengganu Tengah Development Authority (KETENGAH), Kelantan Selatan Development Authority (KESEDAR), Kedah Development Authority (KEDA), Penang Development Authority (PERDA) and Jengka Regional Development Authority (LKWJ) were established between 1972 and 1983 in the states of Pahang, Johor, Terengganu, Kelantan, Kedah and Pulau Pinang by the Federal Government under specific parliamentary legislations to regulate their structure, jurisdictions and operations. Despite the fact that the Federal Government and State Governments have their exclusive and concurrent powers clearly spelt out under the Malaysian Federal Constitution, the establishment of the aforementioned regional development authorities also underwent jurisdictional and bureaucratic conflicts between the two Governments which resulted in certain governance issues, particularly in the state of Pahang where DARA and LKWJ were located and thereafter dissolved under Acts 569 and 567 respectively in the year 1997. While the idea to revive DARA and LKWJ was mooted by the Federal Government through the Ministry of Rural Development in 2019, these two entities remain legally dormant as opposed to KEJORA, KETENGAH, KESEDAR, KEDA and PERDA that are still in existence. This paper specifically explores the legislative justifications, political considerations and other related factors behind the incorporation and dissolution of DARA that covered 1.01 million hectares of land, Malaysia's largest regional development authority during its establishment under Act 68 on March 30, 1972.